The BRAF and NRAS mutation prevalence in dermoscopic subtypes of acquired naevi reveals constitutive mitogen‐activated protein kinase pathway activation. (1st January 2018) - Tan, J.M.; Tom, L.N.; Jagirdar, K.; Lambie, D.; Schaider, H.; Sturm, R.A.; Soyer, H.P.; Stark, M.S.
Summary: Background: Acquired naevi can have unique dermoscopic patterns that correspond to distinct microanatomical growth patterns. Previous studies on acquired naevi stratified according to dermoscopic pattern focused on the frequency of somatic BRAF mutations, whereas NRAS mutations remained to be elucidated. Objectives: To investigate the BRAF and NRAS mutation prevalence and activation of the mitogen‐activated protein kinase (MAPK) pathway in distinct dermoscopic subtypes of acquired naevi. Methods: Common mutations present in BRAF and NRAS were assessed in 40 globular, reticular and peripheral rim of globules (PG) subtypes of acquired naevi from 27 participants (19 male, 8 female; mean age 46·7 years) selected from 1261 eligible volunteers. Mutations were determined using the highly sensitive and quantitative QX200 droplet digital™ polymerase chain reaction (ddPCR) system. Results: The BRAF V600E (c.1799T>A or c.1799_1800delTGinsA) and BRAF V600K mutations were detected in 85% ( n = 34/40) of naevi. All BRAF wild‐type naevi (15%; n = 6/40) harboured an NRAS codon 12/13 or 61 mutation. BRAF mutations were present in 92% ( n = 12/13) of globular and 100% ( n = 12/12) of PG naevi, whereas reticular naevi were 67% ( n = 10/15) BRAF ‐ and 33% ( n = 5/15) NRAS ‐mutant ( P = 0·037). Conclusions: We discovered that 100% of the assessed acquired naevi had either a BRAF or NRAS mutation. Using sensitive techniques capable of single‐cell mutation detection, it is likely that all acquired naevi will be mutated for BRAF or NRAS . Because both of these mutations are prevalent in distinct dermoscopic naevus subsets, our study supports the role of the MAPK pathway in the development of benign melanocytic proliferations, indicating that additional genomic events besides somatic mutations in BRAF or NRAS are required for melanoma development.